Electrodeposited WO3/Au photoanodes for photoelectrochemical reactions - Lorna Jeffery Minggu; Nurul Akmal Jaafar; Ng, Kim Hang; Khuzaimah Arifin; Rozan Mohamad Yunus (Penerbit Universiti Kebangsaan Malaysia, 2020)
This work aims to study the effect of gold (Au) loading on the photoelectrochemical behavior of tungsten trioxide (WO3 ) photoelectrodes. The WO3 film has been fabricated via electrodeposition method with constant potential on fluorine doped tin oxide (FTO) glass substrate. The Au nanoparticle loading on WO3 films surface was also prepared by constant potential electrodeposition. Due to the small amount of Au loading, the band gap values of the plasmonized WO3 remained around 2.6 eV. However, during the photoelectrochemical analysis, the photoactivity of the plasmonized WO3 photoelectrodes improved >100% with a minimal amount of Au loading compared to the pristine WO3 . The photocurrent generation was further enhanced with the presence of organic donors (methanol and formic acid). The photocurrent achieved 3.74 mA/cm2 when 1.0 M of formic acid was added. Plausible charge transfer mechanism was suggested.